VICTIMOLOGICAL ASPECT OF A CORRUPTION DEAL - A. A. Ivanova (Russian Journal of Economics and Law)
Objective: to present the author's concept of the victimological aspect of corruption crime.Methods: dialectical method of cognition, mainly the systemic approach (analysis).Results: the article discusses the concept of corruption deal as an unlawful act, statutory offence (bribery and subornation), law abuse by the authorized entity. The illegal (most common), and manipulative types of corruption deals and their mechanisms are defined, as well as the ways of their implementation, which include mutually beneficial, bilateral trade, extortion and initiative, active bribery. The diverse negative effects of corruption on the legal relationships are proved. The danger of the crime deal is shown as the factor of corrupt behavior, and active means of formation of corruption networks, which increases victimogenity of corruption acts, doing harm not only to physical but also legal entities. In accordance with this, the point of view supported and proved that it is necessary to expand the notion of victim of corruption offences to legal persons. The conclusion is made about the feasibility of a legal assessment of corruption deals as a qualifying feature of a criminal offense.Scientific novelty: the article justifies the author's position in relation to an assessment of corruption victimization of the deal; victimological characteristic of a corrupt deals victim are given; critical analysis of basic victimological concepts is made to identify the potential corrupt deals victims and ensure victim safety.Practical significance: the idea is expressed of reorienting public consciousness, views on corruption as a way of solving problems; of changing tolerance to corruption, due to which the legal subjects become victims of corrupt deals; of amending the anti-corruption policies towards more careful attention to the protection of the legal relations subjects against the corruption threat.